2015
DOI: 10.18632/oncotarget.3279
|View full text |Cite
|
Sign up to set email alerts
|

FLT3-ITD confers resistance to the PI3K/Akt pathway inhibitors by protecting the mTOR/4EBP1/Mcl-1 pathway through STAT5 activation in acute myeloid leukemia

Abstract: FLT3-ITD and FLT3-TKD are the most frequent tyrosine kinase mutations in acute myeloid leukemia (AML), with the former associated with poor prognosis. Here, we show that the PI3K inhibitor GDC-0941 or the Akt inhibitor MK-2206 induced apoptosis through the mitochondria-mediated intrinsic pathway more efficiently in hematopoietic 32D cells driven by FLT3-TKD (32D/TKD) than FLT3-ITD (32D/ITD), which robustly activated STAT5. The resistance to GDC-0941 and MK-2206 was gained by expression of the constitutively ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 54 publications
8
54
0
Order By: Relevance
“…Additionally, Pimozide has showed an anticancer effect on other types of cancer: melanoma, CNS tumours, osteosarcoma, neuroblastoma, myeloproliferative neoplasms, breast, lung, prostate, ovarian, colorectal, pancreatic and hepatocellular carcinoma . Although, patients with mental disorders such as schizophrenia are less likely to develop cancer than the general population, there are yet no reports about the cancer incidence specifically in Pimozide users.…”
Section: Pimozidementioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, Pimozide has showed an anticancer effect on other types of cancer: melanoma, CNS tumours, osteosarcoma, neuroblastoma, myeloproliferative neoplasms, breast, lung, prostate, ovarian, colorectal, pancreatic and hepatocellular carcinoma . Although, patients with mental disorders such as schizophrenia are less likely to develop cancer than the general population, there are yet no reports about the cancer incidence specifically in Pimozide users.…”
Section: Pimozidementioning
confidence: 99%
“…The DNA damage was measured by alkaline elution analysis, and cells treated with this combination were more affected than cells treated with Bleomicyn alone . Nogami et al administered 2 μmol/L of Pimozide in myeloid leukaemia and evaluated the numbers of viable cells after trypan blue staining. They verified that Pimozide only modestly reduced the viability of neoplastic cells, but combined treatment with GCD‐0941, a PI3K inhibitor, enhanced the results significantly …”
Section: Pimozide As a Potential Anticancer Agentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that both Janus kinase 1/3–signal transducer and activator of transcription 5 (Jak1/3-STAT5) and phosphoinositide 3-kinase–Akt (PI3K-Akt) signaling pathways are involved in naïve and memory CD8 + T cell maintenance (21, 2225). Thus, we cultured DED-pathogenic memory CD4 + T cells with: IL-7 and IL-15, IL-7 and anti-IL-15 Ab, IL-15 and anti-IL-7 Ab, IL-7, IL-15 and STAT5 inhibitor (pimozide) (26, 27), IL-7, IL-15 and Akt inhibitor (MK-2206) (2729), IL-7, IL-15, STAT5 and Akt inhibitors. After 72 hours, we collected the cells and determined the frequencies of Th17 cells.…”
Section: Resultsmentioning
confidence: 99%